"Une force qui va": Reflections on Gérard Depardieu in Danton. Issue 1 (1st April 2021) - McCANN, BEN
Abstract : Taking as its starting point a 1978 article by film critic Molly Haskell, in which she described Gérard Depardieu as "tactile […] grasping, eating, touching, coming to physical terms with everything in sight", this article considers a largely overlooked Depardieu role, as the committed revolutionary leader Georges Danton in Andrzej Wajda's Danton (1983)—a historical role that reflects the actor's commitment to the relevance of the Revolutionary politician and intellectual. By examining three key scenes, the article scrutinizes Depardieu's acting style (body language, vocal delivery, movement choices) and demonstrates that he is committed to new ways of engaging with the ideological processes of acting. In Danton, Depardieu pivots between a familiar set of performative registers—physical menace and self-regarding sensitivity, timidity and flamboyance, innocence and cunning—so that the performance ultimately serves as a timely reminder of his enduring mythic status in French cinema.